Influenza virus surveillance among young children in São Paulo, Brazil: the impact of vaccination - Cabeça,Tatiane Karen (2014)
This study assessed the presence of influenza virus among young children and the coverage of vaccination from 2010 to 2012 in São Paulo, Brazil. Our results demonstrated a lower rate of influenza detection and a predominance of influenza B. A decrease of coverage vaccination through the surveillance periods was observed.